2020
DOI: 10.3390/met10121610
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Fatigue Analysis Based on Microstructure and Strain Distribution for 7075 Aluminum FSW Joints

Abstract: In order to study on tensile and fatigue fracture mechanism of friction stir welded (FSW) joints, the tensile and fatigue behavior of FSW joints are studied based on the microstructure and strain distribution. The large plastic deformation and fracture occurred in the thermo-mechanically affected zone (TMAZ) on retreating side in tension tests. High contents of shear texture and small angle grain boundary reduce the tensile mechanical property of TMAZ material. The fatigue weak area for FSW joints is affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The SZ of the S10 sample has, typical for the FSW process, a microstructure with equiaxed, ultrafine grains with a size of 6.3 ± 2.9 μm ( Figure 7 g). A similar grain size has been reported by many authors investigating 7075 joined via FSW, including Li (8 μm) [ 22 ], Iwaszko (7.6 ± 1 μm) [ 20 ], Feng (6.7–4.6 μm, depending on parameters) [ 26 ], Yeni (4–6 μm) [ 17 ] and Sun (2 μm) [ 23 ]. It should be noted that the S10 sample is characterized by the highest heat input from all used sets of welding parameters.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The SZ of the S10 sample has, typical for the FSW process, a microstructure with equiaxed, ultrafine grains with a size of 6.3 ± 2.9 μm ( Figure 7 g). A similar grain size has been reported by many authors investigating 7075 joined via FSW, including Li (8 μm) [ 22 ], Iwaszko (7.6 ± 1 μm) [ 20 ], Feng (6.7–4.6 μm, depending on parameters) [ 26 ], Yeni (4–6 μm) [ 17 ] and Sun (2 μm) [ 23 ]. It should be noted that the S10 sample is characterized by the highest heat input from all used sets of welding parameters.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, Li et al investigated stationary shoulder FSW (SSFSW) of AA7075-T651 and, in the best variant, obtained 69% joint efficiency [ 22 ]. Additionally, Sun et al performed a tensile and fatigue analysis of AA7075 FSW joints and reported the largest deformation in the thermo-mechanically affected zone (TMAZ), where the low-hardness zone (LHZ) was localized [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The areas surrounding the AFSD region are directly affected by the thermal input during the AFSD process, but do not experience as much mechanical mixing since these regions are on the outer limits of the interaction zone of the tool. These regions will be referred to as the Thermal Mechanical Affected Zone (TMAZ) and the HAZ, which are also phenomena in FSW [38,39] The interaction zone of the tool is defined by all the areas directly affected by the tool, including the flat parts of the tool face and the teardrop features, as shown in Fig. 1.…”
Section: Microstructural Effects Of the Afsd Repairmentioning
confidence: 99%
“…Similar, results on fatigue crack propagation (FCP) were reported by other authors for friction stir welded aluminum alloys. [21][22][23][24] As per Irwin, the plastic zone ahead of the crack tip will control the crack propagating rate. 41 The bigger the plastic zone higher will be the tendency of crack tip blunting and crack closure, was calculated the radius of the plastic zone (r dp ) = (1 / 3)π(K max / σ y ) 2 as the dynamic radius of the plastic zone, where σ y is the yield stress of base material and K max is the maximum applied stress intensity factor.…”
Section: Fatigue Crack Propagation Behaviormentioning
confidence: 98%
“…As the distribution of the hard particles was non-uniform in WNZ thus it will have lower resistance to FCGR compared to the HAZ. 24 Post-weld aging treatment at 200 °C for 10 h caused the re-precipitation of precipitates in WNZ and TMAZ without abnormal grain growth in WNZ thus improved the mechanical properties and higher ΔK th than as-welded and joint aged at a lower temperature of 190 °C for 10 h. 25 There are many studies reported in the literature on the similar [26][27][28][29][30][31][32][33][34] and dissimilar [35][36][37] FSW of AA7039 aluminum alloy. The influence of welding parameters, in process cooling, BM temper, and heat treatment on the evolution of microstructure, abnormal grain growth, tensile behavior, fatigue, and corrosion behavior has been investigated.…”
Section: Introductionmentioning
confidence: 99%